Genetic associations to germinal centre formation in primary Sjögren's syndrome. Issue 6 (20th April 2013) - Reksten, Tove Ragna; Johnsen, Svein Joar Auglænd; Jonsson, Malin Viktoria; Omdal, Roald; Brun, Johan G; Theander, Elke; Eriksson, Per; Wahren-Herlenius, Marie; Jonsson, Roland; Nordmark, Gunnel
Abstract : Background: Primary Sjögren's syndrome (pSS) is an autoimmune rheumatic disease mainly characterised by focal mononuclear cell infiltration in the salivary and lacrimal glands, and by the symptoms xerostomia and keratoconjunctivitis sicca. Germinal centre-like structures (GC) are found in the minor salivary glands of approximately 25% of patients. In this study, we aimed to assess genetic variations in pSS patients with GC-like formations (GC+) compared with patients without such formations (GC−). Methods: Minor salivary gland biopsies from Swedish and Norwegian pSS patients (n=320) were evaluated for GC-like formations, identifying 76 GC+ and 244 GC− patients. A panel of 1536 single-nucleotide polymorphisms (SNPs) in 107 genes was genotyped. Minor allele frequencies in GC+ and GC− patients were compared using Fisher's exact test, and associations were considered significant when p<4.7×10 −4 and suggestive when p<0.01. Results: In this case-only analysis, we identified two SNPs in CCL11 (eotaxin) associated with GC-like structures (p<4.7×10 −4, OR 0.45 and 0.41, respectively). A haplotype of the two minor alleles was associated with GC status with p=2.6×10 −4, OR 0.40. Suggestive associations (p<0.01) were found in SNPs in the B cell activation and/or GC-formation related genes AICDA, BANK1 and BCL2. Furthermore, SNPs in IL17A, ICA1, PKN1 and SNPs in the NF-κB pathway genes CARD8, IKBKE and TANK were found suggestively associated with GC-like structures. Conclusions: Our findings suggest that genetic variations may explain why ectopic GC-like structures are present in some pSS patients, and support the hypothesis that GC+ and GC− patients represent distinct disease phenotypes.